Gas exchange of coffee trees (Coffea arabica) at hight temperatures in the Cerrado of Goiás (Research, Society and Development, 2020)
Cerrado areas of Goiás may become unfit for coffee cultivation due to the increase in temperature. Studies need to be carried out to identify cultivars suitable for future climatic conditions, and a physiological assessment is essential in this search. Altogether there are 133 cultivars registered with the Ministry of Agriculture, Livestock and Supply (MAPA), thus implying doubts to the producer about the best material for his region. Knowing this, the objective was to evaluate gas exchange of three coffee cultivars in their third harvest, during the times of the year when the air temperature is higher in the edaphoclimatic conditions of Ceres-GO. The experiment was in a 4x3 factorial scheme, with four phenological stages (Floral Induction, Flowering, Expansion I and Expansion II), and three genotypes (Obatã Vermelho IAC 1669-20, Paraíso MG 419-1 and IBC-Palma II), which were selected taking into account the productivity in the previous harvest, being the highest, average and lowest respectively. The variables consisted of the liquid photosynthetic rate (µmol.m-2.s-1), transpiration (µmol.m-2.s-1) and stomatal conductance (µmol.m-2.s-1). Photosynthetically active radiation (µmol.m-2.s-1), leaf temperature (°C) and air temperature (°C) were monitored. The data were submitted to ANOVA and compared by Tukey's test at 5% probability. High temperatures combined with water deficit result in photosynthetic inhibition. High leaf and air temperatures lead to photosynthetic reduction and stomatal opening. The cultivars Paraíso MG 419-1 and Obatã Vermelho IAC 1669-20 express higher photosynthetic rates in the Expansion phases, while IBC Palma II obtained greater activity in Flowering.